PELATIHAN PRAKTIKUM BERBASIS INQUIRY BAGI GURU MGMP KIMIA DI KABUPATEN KEDIRI - Novita, Dian (Universitas Negeri Surabaya, 2020)
The results of the initial situation analysis show that there are still many chemistry teachers who aremembers of the Kediri Regency Chemical MGMP who have not yet carried out practical activities.Practicum is still felt as an activity that is burdensome and time-consuming, both in terms of preparation ofpracticum instructions and tools and materials used. One alternative is to provide understanding andexamples of interesting practicum and still be able to practice skills and knowledge. The choice of inquirylearning model is based on the fact that inquiry-based practicum will encourage students to be activelyinvolved in discovering their own concepts or knowledge through practicum using scientific methods thatare assisted by practical instructions. Based on the community service activities that have been carriedout, it can be concluded that this community service activity has proceeded as planned. Based on theresults of the questionnaire, this service activity is very useful for partners in an effort to improveunderstanding of teacher competencies, particularly regarding understanding of inquiry, inquiry-basedpracticum, and using pipette and burette tools as a means to improve the competence of chemistryteachers who are members of the MGMP. Even based on the results of further questionnaires, partnersexpect increased activity, in terms of quantity, or in terms of other material delivery.